A Study on Aerodynamics and Stability Characteristics of a Bell-Shaped Span-Load Wing - Zulkafli, Mohd Fadhli; Ab Razak, Nadhiratul Akmal (Progress in Aerospace and Aviation Technology, 2021)
The existence of the new bell-shaped span-load wing is said to has the best lift distribution especially comparing to the elliptical wing. Bell-shaped span-load wing is designed by configuring the twist of the wing. However, the information on the aerodynamic and stability characteristics of the bell-shaped span-load wing is limited. Thus, the main purpose of the research is to evaluate the aerodynamic and stability characteristic to strengthen the claim of the capability of bell-shaped span-load wing in producing minimum induced drag. As the research is expected to be beneficial to the aviation design team, detailed information regarding the lift distribution as well as the induced drag produced is analysed at the optimum angle of attack and the results is further explained in this research. The numerical method for the analysis is done by using Lifting Line Theory (LLT) in the XFLR5 software which can analyse the wings of aircraft in terms of its aerodynamic and stability characteristic. Then, the comparison of the aerodynamic characteristics for bell-shaped span-load, elliptical span-load and tapered wing done in this research is to strengthen the appeal made stating that the bell-shaped span-load wing is the best type of wing ever existed and may replace the elliptical wing as the best wing shape with aerodynamically most efficient. The research has proven that along the wingspan, the bell-shaped span-load wing produced the lowest and minimum induced drag when being compared. At the optimum angle of attack of bell-shaped span-load wing, though the lift produced is slightly lower than the elliptical and tapered wing, the difference in the induced drag is obvious as bell-shaped span-load wing produces induced drag that is lower than 0. In other words, starting from the semi span of the wing to the wingtip, the bell-shaped span-load wing managed to be the most aerodynamically efficient wing.